Transformation of Customary Law Community Structure in Internal and External Dynamics from the Perspective of Islamic Law - Azzahra, Tsania Putri; Ridwansyah, Moh. Haikal; Santoso, Zaidan Ramadhan; Ilmania, Nurika Falah; Ali, Salih Awadh (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2025)
The structure of customary law societies is a fundamental element in the traditional social system that governs the lives of local communities in Indonesia. This research aims to analyze how the structure undergoes transformation due to internal dynamics as well as external pressures derived from the penetration of state laws, development programs, globalization, and economic investment. This research is normative research using a literature study and document analysis approach. The data collected on indigenous peoples in Indonesia are analyzed deductively with Islamic legal theory. This study found that the structure of indigenous peoples is not static but adaptive, undergoing complex changes. External intervention often weakens indigenous authorities, causes agrarian conflicts, and triggers disharmony between traditional values and the demands of modernity. However, indigenous peoples also show resilience through institutional revitalization, strengthening cultural identity, and efforts to gain legal recognition. From the perspective of Islamic law, customs that do not contradict the sharia are legitimate under the principles of 'urf and the rules of al-'ādah muḥakkamah. The analysis of maqāṣid al-syarī'ah shows that the protection of property, the soul, the intellect, and descendants must serve as the basis for assessing changes in the customary structure. Therefore, harmonization between customary law, Islamic law, and national law is essential to realize an inclusive and equitable legal system.